Growth‐Rate‐Dependent Properties of GaSb/GaAs Quantum Dots on (001) Ge Substrate by Molecular Beam Epitaxy. Issue 1 (8th October 2018) - , Zon; Phienlumlert, Pakawat; Thainoi, Supachok; Kiravittaya, Suwit; Tandaechanurat, Aniwat; Nuntawong, Noppadon; Sopitpan, Suwat; Yordsri, Visittapong; Thanachayanont, Chanchana; Kanjanachuchai, Songphol; Ratanathammaphan, Somchai; Panyakeow, Somsak; et al.
Abstract : Tuning growth of nanostructures can provide additional routes to engineer their characteristics. In this work, the authors report on a combined growth of GaSb/GaAs quantum dots (QDs) and growth of GaAs on (001) Ge substrate. Surface decorated with GaAs anti‐phase domain is the initial template to investigate the growth‐rate effects on the growth of self‐assembled GaSb QDs. By varying the GaSb growth rates, QD ensembles with different morphologies are formed. Perpendicular alignment of elongated GaSb QDs is observed. Cross‐sectional transmission electron microscopic images show a substantial reduction of lateral QD size when it is buried in GaAs matrix. Raman scattering as well as power‐dependent photoluminescence spectroscopies are performed to reveal the optical properties of the nanostructures. Type‐II band alignment characteristic is confirmed. Abstract : Combined growth of GaSb quantum dots (QDs) and GaAs on (001) Ge substrate is reported. By varying the growth rates, QD ensembles with different morphologies are formed. Perpendicular alignment of elongated GaSb QDs is observed. Power‐dependent photoluminescence (PL) spectroscopies reveal the optical properties of the nanostructures. Type‐II band alignment characteristic is confirmed.